Nivel de conocimiento y el grado de cumplimiento en ecoeficiencia en trabajadores administrativos del instituto superior tecnológico Pedro A. Del Águila Hidalgo Iquitos 2022 - Ruiz Ramos, Surecht Alberto (2024)
The general objective of this research work was to determine the relationship between the level of knowledge and the degree of compliance in eco-efficiency in the administrative staff of the I.S.T. Pedro A. Del Águila Hidalgo 2023. The research was quantitative, simple relational and non-experimental in design. . The target population of the study was considered to be the total of administrative workers, and the sample was equal to 34 workers, inclusion and exclusion criteria were taken into account, using the survey as a technique and as the applied instrument were two questionnaires of fifteen and twenty and two items, which passed the validity tests using the Aiken Validity index and reliability with the Crombach's Alpha test and the two halves test with the Pearson r statistic. The data were analyzed, processed and tabulated using the SPSS v27 statistical package. The results indicated that the level of knowledge in eco-efficiency in general in electrical energy, solid waste and paper and related waste is regular or low, the level of knowledge in eco efficiency according to gender and level of education is regular and low. The degree of partial compliance or sometimes compliance with eco-efficiency was the one that predominated in general, and according to gender and level of education. The degree of partial compliance or sometimes compliance with eco-efficiency was the one that predominated in electric energy eco-efficiency , solid waste and paper and related items. No significant association was found between the level of knowledge and the degree of compliance in eco-efficiency in general and between the dimensions of electrical energy, solid waste and paper and related items at a probability level of 0.05.